2011
DOI: 10.1021/ol202284n
|View full text |Cite
|
Sign up to set email alerts
|

N-Prolinylanthranilamide Pseudopeptides as Bifunctional Organocatalysts for Asymmetric Aldol Reactions

Abstract: Proline anthranilamide-based pseudopeptides were shown to be effective organocatalysts for enantioselective direct aldol reactions of a selection of aldehydes with various ketones with excellent yield, enantioselectivity up to 99% and anti to syn diastereoselectivity up to 25:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Barbas and co‐worker studies showed that the simple L ‐prolinamide with the acidic nature of the –CONH proton is less, therefore it is an ineffective catalyst for the aldol rection . To overcome this problem a range of prolinamide derivatives including di‐ and tri‐peptides were developed to be excellent catalysts for asymmetric transformation . Synthetic peptides have the advantage of designable modularity, are readily available, and they are made up from the same chiral building blocks (amino acid residues) as enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Barbas and co‐worker studies showed that the simple L ‐prolinamide with the acidic nature of the –CONH proton is less, therefore it is an ineffective catalyst for the aldol rection . To overcome this problem a range of prolinamide derivatives including di‐ and tri‐peptides were developed to be excellent catalysts for asymmetric transformation . Synthetic peptides have the advantage of designable modularity, are readily available, and they are made up from the same chiral building blocks (amino acid residues) as enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…designed bifunctional pseudopeptides N ‐prolinylanthranilamide for direct asymmetric aldol reaction. The anthranilic acid core represents a very convenient template for structural motif, in the present case modification of the carboxylic acid by incorporation of an amino acid residue, which was found to be excellent organocatalyst for aldol reaction of 4‐nitrobenzaldehyde 10 with cyclohexanone 11 and anti aldol product 13 was obtained with (9:1) dr and 99% ee (Scheme ) …”
Section: Prolinamide Catalysed Direct Asymmetric Aldol Reactionmentioning
confidence: 89%
“…Pearson and Panda synthesised a series of N ‐prolinylanthranilamide pseudopeptides using L ‐proline and anthranilic acid core unit as organocatalysts for asymmetric aldol reaction of isatin with acetone. These organocatalysts also applicable for a variety of isatin derivatives and acetone to afforded corresponding aldol product in high yield and good enantioselectivity (Scheme ) …”
Section: Prolinamide Catalysed Direct Asymmetric Aldol Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, huge efforts have been made to modify L-proline and 4-hydroxy-L-proline to prepare organocatalyst for aqueous medium asymmetric aldol reaction. Primarily, three types of modifications on the basic skeletons of L-proline and 4-hydroxy-L-proline were reported [29][30][31][32]. Carboxylic acid moiety of L-proline, hydroxyl group of 4-hydroxy-L-proline individually or both groups simultaneously were reported to be modified in order to enhance the hydrophobicity of L-proline.…”
Section: Introductionmentioning
confidence: 99%